Spotlight on Gladue: Challenges, Experiences, and Possibilities in Canada’s Criminal Justice System (Department of Justice Canada, 2017)
'In view of the implications of the Gladue and Ipeelee decisions for Canada's criminal justice system, this paper was designed to meet the following objectives: to provide a brief statistical overview on the overrepresentation of Indigenous persons in the Canadian correctional system, a summary of the legislative reforms that led to s. 718.2(e), and an overview of the court's interpretation in Gladue and Ipeelee; to analyze the key issues in the literature regarding the application of s. 718.2(e), and the Gladue and Ipeelee decisions in sentencing Indigenous individuals; to describe the justice system initiatives and programs that have been put in place to support the application of s. 718.2(e) in Canadian provinces and territories; and to summarize the studies on the experiences of members of the court system and Indigenous accused who have participated in Indigenous justice system initiatives"--Objectives, p. 5-6.